2017
DOI: 10.1371/journal.pone.0179702
|View full text |Cite
|
Sign up to set email alerts
|

The best encouraging persons in labor: A content analysis of Iranian mothers' experiences of labor support

Abstract: Background and aimsThe process of giving birth is very stressing for the mother. Meanwhile, maternity ward staff’s lack of awareness of mothers’ fears make mothers feel lonely and helpless. This study aimed to explore women’s perceptions of labor support during vaginal delivery.Materials and methodsThis exploratory qualitative study used qualitative content analysis to explore Iranian mothers’ experiences of labor support. Data were collected using observations and semi-structured interviews with 25 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 30 publications
(44 reference statements)
3
44
1
5
Order By: Relevance
“…However, some midwives found it difficult to engage as carers with women when doulas were present, as they felt that doulas encroached on their carer role.Akhavan 2012b; Lundgren 2010; McLeish 2018; Stevens 2011Low confidenceDue to minor concerns regarding coherence, moderate concerns regarding methodological limitations and adequacy, and serious concerns regarding relevance13Lay companions received little or no training on how to support the woman during labour and childbirth, which made them feel frustrated.Kululanga 2012; Sapkota 2012Low confidenceDue to minor concerns regarding methodological considerations and coherence, and serious concerns regarding relevancy and adequacy14Some men felt that they were actively excluded, left out, or not involved in their female partner's care. They were unsure of where they fit in to support the woman, and felt that their presence was tolerated but not necessary.Bäckström 2011; Chandler 1997; Kaye 2014; Kululanga 2012; Longworth 2011; Somers‐Smith 1999Moderate confidenceDue to minor concerns regarding coherence, and moderate concerns regarding methodological limitations, relevance and adequacy Roles that companions play Informational support 15Women valued the non‐pharmacological pain relief measures that companions helped to facilitate, including a soothing touch (holding hands, massage and counter pressure), breathing, and relaxation techniques.Campero 1998; Chapman 1990; Dodou 2014; de Souza 2010; Fathi 2017; Hunter 2012; Kabakian‐Khasholian 2015; Khresheh 2010; Lundgren 2010; McLeish 2018; Sapkota 2013; Sapkota 2012; Somers‐Smith 1999; Thorstensson 2008; Torres 2015High confidenceDue to minor concerns regarding adequacy, coherence, and relevance, and moderate concerns regarding methodological limitations16Doulas played an important role in providing information to women about the process of childbirth, duration of labour, and reasons for medical interventions. They bridged communication gaps between clinical staff and women, and facilitated a more actively engaged environment where women were encouraged to ask questions.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some midwives found it difficult to engage as carers with women when doulas were present, as they felt that doulas encroached on their carer role.Akhavan 2012b; Lundgren 2010; McLeish 2018; Stevens 2011Low confidenceDue to minor concerns regarding coherence, moderate concerns regarding methodological limitations and adequacy, and serious concerns regarding relevance13Lay companions received little or no training on how to support the woman during labour and childbirth, which made them feel frustrated.Kululanga 2012; Sapkota 2012Low confidenceDue to minor concerns regarding methodological considerations and coherence, and serious concerns regarding relevancy and adequacy14Some men felt that they were actively excluded, left out, or not involved in their female partner's care. They were unsure of where they fit in to support the woman, and felt that their presence was tolerated but not necessary.Bäckström 2011; Chandler 1997; Kaye 2014; Kululanga 2012; Longworth 2011; Somers‐Smith 1999Moderate confidenceDue to minor concerns regarding coherence, and moderate concerns regarding methodological limitations, relevance and adequacy Roles that companions play Informational support 15Women valued the non‐pharmacological pain relief measures that companions helped to facilitate, including a soothing touch (holding hands, massage and counter pressure), breathing, and relaxation techniques.Campero 1998; Chapman 1990; Dodou 2014; de Souza 2010; Fathi 2017; Hunter 2012; Kabakian‐Khasholian 2015; Khresheh 2010; Lundgren 2010; McLeish 2018; Sapkota 2013; Sapkota 2012; Somers‐Smith 1999; Thorstensson 2008; Torres 2015High confidenceDue to minor concerns regarding adequacy, coherence, and relevance, and moderate concerns regarding methodological limitations16Doulas played an important role in providing information to women about the process of childbirth, duration of labour, and reasons for medical interventions. They bridged communication gaps between clinical staff and women, and facilitated a more actively engaged environment where women were encouraged to ask questions.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Companions encouraged and helped women to mobilise throughout labour or to change positions, such as squatting or standing, and provided physical support to go to the bathroom or adjust clothing.Afulani 2018; Chandler 1997; Chapman 1990; de Souza 2010; Fathi 2017; Hunter 2012; Kabakian‐Khasholian 2015; Khresheh 2010; Koumouitzes‐Douvia 2006; McLeish 2018; Premberg 2011; Price 2007; Sapkota 2012; Shimpuku 2013; Torres 2013High confidenceDue to minor concerns regarding coherence, relevance and adequacy, and moderate concerns regarding methodological limitations21Companions played an important role to assist healthcare providers to care for women by observing and identifying potential issues throughout labour and childbirth.Akhavan 2012b; Alexander 2014; Khresheh 2010; Qian 2001; Sapkota 2012; Shimpuku 2013Moderate confidenceDue to minor concerns regarding coherence and relevance, and moderate concerns regarding methodological limitations and adequacy22Some healthcare providers and doulas felt that shortcomings in maternity services could be potentially addressed by doulas or lay companions.Afulani 2018; Akhavan 2012b; Stevens 2011Very low confidenceDue to minor concerns regarding coherence, moderate concerns regarding methodological limitations, and serious concerns regarding relevance and adequacy Emotional support 23Women valued that companions and doulas helped to facilitate their feeling in control during labour and gave them confidence in their abilities to give birth.Berg 2006; Campero 1998; Chapman 1990; Darwin 2016; Dodou 2014; Fathi 2017; Gilliland 2011; Hunter 2012; Ledenfors 2016; Price 2007; Sapkota 2012Moderate confidenceDue to minor concerns regarding adequacy and coherence, and moderate concerns regarding methodological limitations and rel...…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…However, these aspects did not impede or restrict the companion from performing his or her role as provider of support to the woman, especially in relation to the emotional dimension. Providing emotional support was also mentioned in other studies as activities which calm, encourage, transmit security and mitigate the woman’s pain 6 , 10 , 17 , 20 - 22 . …”
Section: Discussionmentioning
confidence: 97%
“…The presence of the father in this scenario symbolizes - even if only partially - the family’s becoming closer after the birth. International studies have revealed that in other countries, the presence of the father during the birth is accepted 17 , regardless of whether this is related or not to the provision of support, it frequently being the case that the doula or midwife takes on this task 18 - 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It was conducted from April to September 2016 to validate the supportive care plan for mothers in labor and delivery wards developed using a qualitative study (16). In the 1st stage of the program development, the program components were taken from the findings of a qualitative approach; i.e., grounded theory study.…”
Section: Methodsmentioning
confidence: 99%